Osimertinib-Centered Therapy Against Uncommon Epidermal Growth Factor Receptor-Mutated Non-Small-Cell Lung Cancer- A Mini Review - Song, Chengyang; Yang, Xueying (Frontiers in Oncology, 2022)
Osimertinib is a third-generation, irreversible mutant epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor that is approved by the U.S. Food and Drug Administration (FDA) and European Medicines Agency (EMA). Osimertinib is currently the first line drug recommended by National Comprehensive Cancer Network (NCCN) guidelines against lung cancer harboring the EGFR TKI-sensitive mutation and acquired EGFR T790M resistance mutation. Osimertinib demonstrated some efficacy in clinical trials and case reports in patients bearing certain uncommon EGFR mutations, but it is not active in patients with other mutations such as C797S and S768I. This mini-review presents the mechanisms underlying the variations in patient responses, discusses the use of osimertinib against non-small-cell lung carcinomas with uncommon EGFR mutations, and addresses the future prospects of osimertinib-centered therapy.